Prevalence and Clinical Characteristics of Alopecia Areata at a Tertiary Care Center in Saudi Arabia - Aysha A. Alshahrani; Rawan Al-Tuwaijri; Zainah A. Abuoliat; Mesnad Alyabsi; Mohammed I. AlJasser; Rayan Alkhodair (Dermatology Research and Practice)
Introduction. Alopecia areata (AA) is a common autoimmune disorder of hair follicles characterized by patches on nonscarring hair loss. Reports of prevalence and clinical characteristic of AA in Saudi Arabia are limited. The aim of our study is to describe the prevalence and clinical characteristics of Saudi patients with AA. Materials and Methods. A retrospective cross-sectional study was conducted at King Abdulaziz Medical City in Riyadh, Saudi Arabia. All patients diagnosed with AA between January 2016 and December 2017 were included. Data included patient demographics, type of AA, disease duration, family history of AA, and comorbid autoimmune diseases. Results. A total of 216 patients with AA were included. The overall prevalence of AA was approximately 2.3%. The mean disease duration at the time of presentation was 2 months while the mean age of onset was 25.61 years. The most common type of AA in both adult and pediatric groups was the patchy type involving the scalp. Comorbid diseases were found in 32.41% of patients. Common associated conditions included hypothyroidism, diabetes mellitus, and atopic diseases. Conclusion. The overall prevalence of AA among a population of Saudi patients is 2.3%. AA prevalence is higher in pediatrics than adults. Common comorbid conditions include hypothyroidism, diabetes mellitus, and atopic diseases.